2011
DOI: 10.1371/journal.pone.0025798
|View full text |Cite
|
Sign up to set email alerts
|

Incentive or Habit Learning in Amphibians?

Abstract: Toads (Rhinella arenarum) received training with a novel incentive procedure involving access to solutions of different NaCl concentrations. In Experiment 1, instrumental behavior and weight variation data confirmed that such solutions yield incentive values ranging from appetitive (deionized water, DW, leading to weight gain), to neutral (300 mM slightly hypertonic solution, leading to no net weight gain or loss), and aversive (800 mM highly hypertonic solution leading to weight loss). In Experiment 2, a down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
1
19
0
1
Order By: Relevance
“…Altogether, all these results indicate that amphibians, unlike mammals, follow a simple rule in which the strength of behavior during extinction is a direct function of reward magnitude during acquisition (Muzio et al, 1992(Muzio et al, , 2011). Amsel's (1992) frustration theory claims that paradoxical reward effects involve an emotional response of frustration due to the unexpected absence or devaluation of the reward.…”
Section: Overtraining Extinction Effectmentioning
confidence: 79%
See 1 more Smart Citation
“…Altogether, all these results indicate that amphibians, unlike mammals, follow a simple rule in which the strength of behavior during extinction is a direct function of reward magnitude during acquisition (Muzio et al, 1992(Muzio et al, , 2011). Amsel's (1992) frustration theory claims that paradoxical reward effects involve an emotional response of frustration due to the unexpected absence or devaluation of the reward.…”
Section: Overtraining Extinction Effectmentioning
confidence: 79%
“…After a few trials, the response recovers and both groups tend to respond similarly (e.g., Crespi, 1942;Elliott, 1928;Pellegrini &Mustaca, 2000;Pellegrini, Ruetti, Mustaca, &Muzio, 2004). Unlike in mammals, incentive devaluation in amphibians results in a gradual adjustment of their response to the level of the unshifted group, without going through a period of poorer performance (e.g., Muzio et al, 1992Muzio et al, , 2011. This effect is referred to as reversed successive negative contrast.…”
Section: Successive Negative Contrastmentioning
confidence: 99%
“…The day before pretraining, standard weights (weight of the hydrated toad with its urinary bladder empty; Ruibal, 1962) of all toads were obtained. These weights varied between 50 and 102 g. To induce watersearch behavior, toads were dehydrated to 80% of their standard weights at the beginning of each pretraining and training session (a standard method employed in this species; e.g., see Muzio et al, 2011;Muzio, Segura, & Papini, 1992). This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental subjects began their training sessions dehydrated to 80% of their standard weight, a procedure widely used to motivate toads to search for water as a primary reinforcer [e.g. Muzio et al, 2011]. The inexperienced control subjects were also dehydrated.…”
Section: Subjectsmentioning
confidence: 99%
“…Nonetheless, previous work on cognition in the terrestrial toad Rhinella arenarum demonstrated considerable learning abilities [e.g. Muzio et al, 1992Muzio et al, , 2011, particularly with regard to spatial learning and memory [Daneri et al, 2011[Daneri et al, , 2015. Though less complex compared to that of amniotes [e.g.…”
Section: Introductionmentioning
confidence: 99%